2014
DOI: 10.3390/ijms15057563
|View full text |Cite
|
Sign up to set email alerts
|

Topical N-Acetylcysteine Accelerates Wound Healing in Vitro and in Vivo via the PKC/Stat3 Pathway

Abstract: N-Acetylcysteine (Nac) is an antioxidant administered in both oral and injectable forms. In this study, we used Nac topically to treat burn wounds in vitro and in vivo to investigate mechanisms of action. In vitro, we monitored glutathione levels, cell proliferation, migration, scratch-wound healing activities and the epithelialization-related proteins, matrixmetalloproteinase-1 (MMP-1) and proteins involved in regulating the expression of MMP-1 in CCD-966SK cells treated with Nac. Various Nac concentrations (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 30 publications
(31 reference statements)
10
47
0
Order By: Relevance
“…Consistent with our observation, NAC has also been observed to promote cellular proliferation in adipose-derived stem cells, which hold great promise for wound repair and regeneration [16]. In addition, a recent study has also reported that NAC enhanced cellular proliferation as well as scratch wounding healing in CCD966SK cells (human skin fibroblast cell line) [1]. We also observed that increased cellular proliferation induced by NAC during wound healing was paralleled with increased levels of MnSOD protein expression and activity.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Consistent with our observation, NAC has also been observed to promote cellular proliferation in adipose-derived stem cells, which hold great promise for wound repair and regeneration [16]. In addition, a recent study has also reported that NAC enhanced cellular proliferation as well as scratch wounding healing in CCD966SK cells (human skin fibroblast cell line) [1]. We also observed that increased cellular proliferation induced by NAC during wound healing was paralleled with increased levels of MnSOD protein expression and activity.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, the effect of NAC on extracellular matrix (ECM) remodeling during wound healing has also been reported. Topical NAC administration has been demonstrated to accelerate burn wound healing through induction of collagenous expression of matrixmetalloproteinase-1 (MMP-1) via protein kinase C (PKC) signaling pathway, which has been implicated in pathologies involving ECM remodeling [1]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 MinLing Tsai et al reported that the topical administration of 3% NAC was significantly effective on the cell proliferation, migration, scratch wound healing, and collagenous expression of MMP-1 via the PKC/ Stat3 signaling pathway. 9 In addition, topical NAC 8% eye drops have also been reported to improve the initial treatment of experimental alkali corneal burns. 22 In our study, better wound healing ratios and epithelialization ratios were obtained in the NAC group than in the control group, and the mean fibrosis score was significantly higher in the NAC group than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…This process can be facilitated by a number of natural or artificial agents. 9 However, the wound healing process can be interrupted by a number of factors, which may impair 1 or more stages of the process and thus lead to inappropriate or failed tissue repair. Failed processes of wound healing lead to large amounts of health care expenses, which are estimated to exceed $3 billion per year.…”
Section: Discussionmentioning
confidence: 99%